2019
DOI: 10.1002/jcp.28371
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SOX21‐AS1 promotes cervical cancer progression by competitively sponging miR‐7/VDAC1

Abstract: Growing evidence has shown that long noncoding RNAs (lncRNAs) play crucial roles in cervical cancer. Dy000sregulation of lncRNA SOX21 antisense RNA 1 (SOX21‐AS1) has been reported in several tumors. However, its expression pattern and potential biological function in cervical cancer (CC) have not been investigated. In this study, we first reported that SOX21‐AS1 expression was significantly upregulated in both CC tissues and cell lines. High expression of SOX21‐AS1 was found to be significantly correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 30 publications
3
31
0
1
Order By: Relevance
“…They can function as molecular sponges, scaffolds, and guides for interactions with proteins, mRNAs, or microRNAs (miRNAs), thereby regulating the expression of target genes (Anastasiadou et al, 2018). Accumulated evidence indicates that many lncRNAs are aberrantly expressed in cervical cancer (Chen et al, 2019;Zhang X. et al, 2019). Alterations in the expression of lncRNAs are involved in cervical carcinogenesis and cancer progression by playing tumorsuppressive or oncogenic roles (Aalijahan and Ghorbian, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They can function as molecular sponges, scaffolds, and guides for interactions with proteins, mRNAs, or microRNAs (miRNAs), thereby regulating the expression of target genes (Anastasiadou et al, 2018). Accumulated evidence indicates that many lncRNAs are aberrantly expressed in cervical cancer (Chen et al, 2019;Zhang X. et al, 2019). Alterations in the expression of lncRNAs are involved in cervical carcinogenesis and cancer progression by playing tumorsuppressive or oncogenic roles (Aalijahan and Ghorbian, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the pathogenesis of cervical cancer needs to be explored further to discover more therapeutic targets for cervical cancer treatment. LncRNAs have been found to participate in tumorigenesis and play significant roles in cervical cancer 25,26 . E2F4 was identified to be critical in the regulation of cell progression in various cancers and found to be related to cervical cancer 16 .…”
Section: Discussionmentioning
confidence: 99%
“…14 The alteration in the expression of these lncRNAs not only has obvious effects on the biological behaviors such as proliferation, migration and invasion of cervical cancer cells, but is closely related to the tumor size, angiogenesis, Federation of Gynecology and Obstetrics (FIGO) stage, lymph node metastasis and poor prognosis of cervical cancer. 1,15 Thus, regulation of certain lncRNAs can represent a novel therapeutic strategy in the treatment of cervical cancer. For instance, Zhang et al 15 recently reported that lncRNA SOX21 antisense RNA 1 (SOX21-AS1) was significantly upregulated in both cervical cancer tissues and cell lines and high expression of SOX21-AS1 was correlated with FIGO stage, lymph node metastasis and depth of cervical invasion.…”
Section: Discussionmentioning
confidence: 99%
“…1,15 Thus, regulation of certain lncRNAs can represent a novel therapeutic strategy in the treatment of cervical cancer. For instance, Zhang et al 15 recently reported that lncRNA SOX21 antisense RNA 1 (SOX21-AS1) was significantly upregulated in both cervical cancer tissues and cell lines and high expression of SOX21-AS1 was correlated with FIGO stage, lymph node metastasis and depth of cervical invasion. They also found that SOX21-AS1 promoted cervical cancer progression and could be used as a potential prognostic biomarker for patients with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%